(untitled) (Economic Journal of Nepal, 2020)
This paper aims to examine the causal relationship between the budget deficit and the current account deficit of Nepal using time series data sets for the period from 1975 to 2019. Based on the Autoregressive Distributed Lag (ARDL) Model, the empirical finding indicates that rising budget deficits put more stress on the current account deficits in the both long-run and the short-run. Furthermore, the Granger Causality test reconfirms that unidirectional causation runs from budget deficit to current account deficit, which supports the conventional theory of the positive relationship between fiscal and external deficits, i.e. the twin deficit hypothesis for Nepal. The probable adverse effects that arise from such kind of relationship in the economy should be incorporated by the government of Nepal and concerned stakeholders by adopting appropriate policy measures as well as its effective implementation.